Europe Dithers Over Digital Radio. - Dumiak, M.
Because of unspecified technical glitches, Digital Radio Mondiale (DRM) technology failed to take off when it was first introduced in 2005. As the 2006 holiday season draws near, DRM advocates are once again optimistic about the prospects of the technology. DRM technology was originally developed as a non-proprietary digital technology for terrestrial broadcasting at frequencies of 30 megahertz and below, to supplement the satellite transmission technologies already in place. Although DRM's sound quality wont match that of true hi-fi, listeners will appreciate having shortwave and AM stations coming in at near-FM quality. More importantly, listeners will be able to get many more stations than before, and if they purchase a well-equipped radio, they will have user-friendly ways to identify and select programs of interest
Keywords: AM broadcasting; Digital Radio Mondiale technology; Europe dithers; Digital broadcasting; Shortwave broadcasting; Signal quality; Terrestrial broadcasting; Transmission technologies; Unspecified technical glitches